Construção de modelo para apoiar à gestão da qualidade de um produto: um estudo de caso - Cechetto, Márcio (2020)
The objective of this Dissertation is to build a model to support the quality management of a product, from the perspective of the managers of a company that manufactures electrical distribution products for civil construction, located in the State of Santa Catarina. This research is characterized for being a case study of qualitative and quantitative nature, of exploratory character, combined with bibliographic and documentary research, having as source of the primary data the semi-structured interview, with the interpretation of the data by the constructivist method. To ensure that the singularities of the context and the values, preferences and motivations of the managers were taken into account, the multicriteria methodology in support of the decision was used - Multicriteria Decision Aid-Constructivist Methodology (MCDA-C) as an intervention instrument and the Knowledge Development Process -Constructivist (ProKnow-C) for the literature review. The constructivist model identified eight strategic objectives that represent the concerns of the managers interviewed: Processes; Resources; Human Resources Management; Policies and Strategies; Product Performance; Impact on Society; Employee Satisfaction and Customer Satisfaction. In this research, we opted to apply the MCDA-C method only in the area of Processes, with an emphasis on product quality. The model allowed the construction of scales to measure and inform the current level of performance (Status Quo and the Goal), as well as generating actions to improve product quality. As a scientific and empirical contribution, this research helps to develop a constructivist model observing the singularities of the environment and guiding the identification and measurement of objectives in the values and preferences of the manager, thus favoring the legitimacy and use of this model, mainly because it presents itself as another option to realistic models found in the literature referenced in this Dissertation.